Regulating Estrangement: Human–Animal Chimeras in Postgenomic Biology. (November 2020) - Hinterberger, Amy
Why do laws and regulations marking boundaries between humans and other animals proliferate amid widespread proclamations of the waning of the species concept and the consensus that life is a continuum? Here I consider a recent spate of new guidelines and regulations in the United Kingdom and United States that work to estrange human bodies from other animals in biomedicine. Using the idea of a bioconstitutional moment to understand how state institutions deliberate over "human–animal chimeras, " I address how nations differently establish separations between humans and other animals. New chimeric entities, containing human hereditary material, have consecrated regulatory ground and signify increased attention to fields of research that have long used interspecies mixing. Regulators and policy makers now find themselves in a curious position. On the one hand, they continue to regulate the estrangement between humans and other animals, but on the other, they support the creation of chimeric life––a form of life that draws into question the very basis of such separations.